การแพร่ของไอโอเดตเข้าสู่แบบจำลองเปลือกไข่ที่เร่งด้วยเทคนิคการนำส่งด้วยไฟฟ้า - กฤตวัตร ธนศักดิ์โกศล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objective of this research is to study factors affecting the diffusion of iodate into an egg by an electro-delivery technique using an eggshell model. The eggshell model was created by replacing egg white and egg yolk with Milli Q water. The model was fixed and sealed to the future board and placed in the middle of the plastic box to divide the box into two compartments; one was for a saturated iodate solution; the other was for Milli Q water. Two electrodes were placed on each side of the eggshell model, where the anode (+) was immersed in Milli Q water and the cathode (-) was immersed in a saturated iodate solution. Under an electrical potential, negatively charged iodate ion would be pushed by the cathode into the eggshell towards the anode. The iodate level in the eggshell model was determined by a capillary electrophoresis method. Factors such as electrical potential, time, and position of the electrodes were studied in this experiment. The result revealed that the iodate level in the eggshell mode was increasing with increased electrical potentials and time. In addition, the electrodes position that was placed adjacent to the eggshell model exhibited higher iodate level than the position that was placed far away from the eggshell model.